2021
DOI: 10.3390/ijms221910296
|View full text |Cite
|
Sign up to set email alerts
|

Human FoxP Transcription Factors as Tractable Models of the Evolution and Functional Outcomes of Three-Dimensional Domain Swapping

Abstract: The association of two or more proteins to adopt a quaternary complex is one of the most widespread mechanisms by which protein function is modulated. In this scenario, three-dimensional domain swapping (3D-DS) constitutes one plausible pathway for the evolution of protein oligomerization that exploits readily available intramolecular contacts to be established in an intermolecular fashion. However, analysis of the oligomerization kinetics and thermodynamics of most extant 3D-DS proteins shows its dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(149 reference statements)
1
2
0
Order By: Relevance
“…Despite their high sequence identity, FoxP4 possesses a higher energy barrier in the association process, corroborating that the dimerization ability relies on the association rather than the dissociation energy barrier. Interestingly, considering the low energy barrier of FoxP proteins compared with other 3D-DS proteins [8,20,24], these results reinforce the observed feasibility to also form 3D-DS heterooligomers [25], suggesting that FoxP proteins could undergo 3D-DS to form heterodimers under physiological conditions [17].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Despite their high sequence identity, FoxP4 possesses a higher energy barrier in the association process, corroborating that the dimerization ability relies on the association rather than the dissociation energy barrier. Interestingly, considering the low energy barrier of FoxP proteins compared with other 3D-DS proteins [8,20,24], these results reinforce the observed feasibility to also form 3D-DS heterooligomers [25], suggesting that FoxP proteins could undergo 3D-DS to form heterodimers under physiological conditions [17].…”
Section: Discussionsupporting
confidence: 69%
“…The crystal structure of FoxP4 revealed a monomer similar to FoxP1 and FoxP2 (root mean square deviations [RMSD] after structural alignment of 1.79 and 0.96 Å, respectively), with high conservation of the characteristic forkhead fold of the Fox family [17] (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Villalobos et al [ 8 ] reviewed another transcription factor, namely human FoxP, and showed that it can serve as a tractable model for the evolution and function of three-dimensional (3D) domain swapping (DS), a common theme in the formation of multimeric protein complexes. Biophysical studies on FoxP have suggested that the dynamics of the polypeptide chain are crucial to decrease the energy barrier of 3D-DS, enabling fast oligomerization.…”
mentioning
confidence: 99%